Tyrosine Kinase Inhibitors - Induced Cutaneous Leukocytoclastic Vasculitis: Vasculite Leucocitoclástica Cutânea Induzida por Inibidores da Tirosina-Cinase - Costa, Diogo Alpuim; Almeida, Susana Baptista de; Barata, Pedro Coelho; Quintela, António; Cabral, Pedro; Afonso, Ana; Silva, João Maia (Gazeta Médica, 2018)
A 66-year-old patient with metastatic renal clear cell carcinoma, developed palpable purpura during systemic treatment with different tyrosine kinase inhibitors (TKI).